Psycholinguistic aspects of representing aggression in wartime media discourse - Kovalchuk, Liudmyla; Litkovych, Yuliia (East European Journal of Psycholinguistics, 2022)
The article focuses on aggression caused by the Russian-Ukrainian war as a vivid phenomenon in media discourse. The paper reveals the psychological aspects of this phenomenon, the reasons for the use of verbal aggression, its forms, and its impact on recipients. The research also explores lexical and stylistic means of representing aggression in the Ukrainian media discourse: online publications in periodicals and posts on social media such as Facebook, Twitter, and Instagram. It has been identified that the frequently used invective vocabulary and creolized memes in the media are specific verbal and nonverbal means of psychological liberation from aggression and destructive influence on the target audience. Based on the results of a survey involving 100 respondents from different regions of Ukraine, 50 of whom were male and 50 female, it was found that aggression serves to expose such dominant negative emotions evoked by the Russian-Ukrainian war as anger and hatred. However, the object of aggression of the people surveyed is strikingly different: for 58 % of men it’s the Russian president, while for 52 % of women – the Russian troops. When asked about the most common forms of aggression, the majority of the respondents claimed that it is expressed by mockery, curses and obscenity. The survey documented the use of the corresponding war-related emotionally charged vocabulary, including neologisms with various word-building patterns and newly formed set phrases, by both females and males to express their aggression verbally. Additionally, the participants of the survey confirmed that creolized memes are effective functional tools with nearly equally distributed percentage of protesting against the war, ridiculing invaders and resisting the Russian propaganda.Disclosure Statement No potential conflict of interest was reported by the authors.
Keywords: aggression; wartime media discourse; verbal means; nonverbal means; creolized memes